Filmes poliméricos de ácido cítrico e etilenoglicol: síntese e caracterização estrutural e óptica - Andrade Junior, Nelson Moreira de [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Carbon-based luminescent materials have gained increasing attention over the past decades due to their unique combination of low cost, chemical stability, abundance of raw materials, and versatile optical properties. Among the promising synthesis routes, those employing simple organic precursors such as citric acid and ethylene glycol stand out, as they can form polyester-type polymers that, when subjected to controlled thermal treatment, give rise to carbonaceous structures containing sp² domains and emissive centers associated with surface states. These materials represent a sustainable alternative to conventional metal-based phosphors used in optoelectronic and white-light-emitting devices. In this work, the formation and structural modification of hybrid carbon films produced by the reaction between citric acid and ethylene glycol were investigated. The films were obtained through controlled thermal treatment at 230°C for 30 minutes, with a heating rate of 1°C/min. Deposition was performed by the dip-coating method at three different speeds 1.02 cm/min, 15.88 cm/min, and 31.75 cm/min, in order to assess the effects of film thickness and homogeneity on the optical and structural response. Subsequently, the samples were subjected to laser writing using 532 nm and 405 nm excitation sources at varying power levels to induce local transformations, promote partial reduction of graphene oxide (GO), and modulate the formation of graphitic domains. Raman spectroscopy revealed the characteristic D (~1325 cm⁻¹), G (~1580 cm⁻¹), and 2D (~2650–2670 cm⁻¹) bands of carbon-based materials. The evolution of the I(D)/I(G), I(D′)/I(G), and I(D″)/I(G) ratios allowed the correlation between the degree of structural disorder and carbon hybridization as a function of the writing power and deposition speed. At higher laser powers, the predominance of the G band indicated greater order and the presence of sp² domains, consistent with the formation of partially reduced graphene oxide (rGO), as described by López-Díaz et al 1. At intermediate powers, the enhancement of the D band and the partial disappearance of the 2D band suggested increased disorder and oxidation, leading to structures consistent with GO, in agreement with Sadezky et al 2 and Wu et al 3. At lower powers, the reappearance of a weak 2D band and the decrease of I(D)/I(G) indicated partial reorganization of sp² regions, suggesting the onset of structural reduction and rearrangement. The laser writing process using the 532 nm source promoted greater carbon network reorganization and partial removal of oxygen-containing groups, leading to more ordered graphitic regions. Samples irradiated with this wavelength exhibited narrower G bands and lower I(D″)/I(G) and I(D*)/I(G) ratios, confirming a higher proportion of sp² carbon and the formation of rGO-like regions. Conversely, the 405 nm laser produced more oxidized and disordered structures, characterized by higher I(D)/I(G) ratios and stronger D″ and D* contributions, associated with C–O, C=O, and C–OH groups evidence of functionalized GO formation with a high density of structural defects. This behavior was attributed to the higher photon energy at 405 nm, capable of breaking C–C and C–O bonds and promoting local oxidation reactions. Photoluminescence analyses complemented the Raman results, revealing intense emissions in the 420–600 nm range, attributed to radiative recombination in carbonyl-related surface states and nanodomains resembling carbon quantum dots (CQDs). Films treated near 240°C and written at intermediate power levels exhibited white-light emission under UV-vis excitation, resulting from the superposition of multiple emissive centers and the balanced coexistence of emissive sp² domains and oxygenated groups. This behavior highlights the crucial role of laser energy in modulating electronic states and enabling tunable broadband visible emission. Deposition speed also influenced the resulting structure and emission. Films prepared at 1.02 cm/min were more uniform and exhibited stronger spectral responses, while those produced at higher speeds (15.88 and 31.75 cm/min) displayed increased structural heterogeneity, reflected in broader I(D)/I(G) dispersion and reduced photoluminescence intensity. Overall, the combined use of thermal treatment and laser writing proved to be an effective and controllable route for tuning the oxidation degree, structural order, and optical properties of carbon-based films. Understanding the interplay between laser-induced reduction, oxidation, and carbon reorganization enables the rational design of luminescent carbon materials with tailored emission properties and structural configurations. The obtained films show potential for applications in optoelectronic and photonic devices, such as white LEDs, sensors, and sustainable emissive coatings, standing out for the low cost and environmentally friendly nature of the synthesis method.

Os materiais luminescentes à base de carbono têm recebido crescente atenção nas últimas décadas devido à sua combinação singular de baixo custo, estabilidade química, abundância de matéria-prima e versatilidade de propriedades ópticas. Entre as rotas de síntese promissoras, destacam-se os processos que utilizam precursores orgânicos simples, como o ácido cítrico e o etilenoglicol, capazes de originar polímeros de natureza poliéster que, quando submetidos a tratamento térmico controlado, dão origem a estruturas carbonosas contendo domínios sp² e centros de emissão associados a estados de superfície. Tais materiais representam uma alternativa sustentável aos compostos metálicos convencionais empregados em dispositivos optoeletrônicos e emissores de luz branca. Neste trabalho, investigou-se a formação e a modificação estrutural de filmes híbridos de carbono produzidos pela reação entre ácido cítrico e etilenoglicol, seguida de tratamento térmico a 230°C por 30 minutos, com taxa de aquecimento de 1°C/min. Os filmes foram obtidos pelo método de dip-coating, variando-se a velocidade de deposição entre 1,02 cm/min, 15,88 cm/min e 31,75 cm/min, a fim de avaliar os efeitos da espessura e da homogeneidade na resposta óptica e estrutural. Posteriormente, as amostras foram submetidas à escrita a laser utilizando fontes de 532 nm e 405 nm em diferentes potências, com o objetivo de induzir transformações locais, promover a redução do óxido de grafeno e modular a formação de domínios grafíticos. As análises espectroscópicas Raman permitiram identificar as bandas D (~1325 cm⁻¹), G (~1580 cm⁻¹) e 2D (~2650–2670 cm⁻¹), características de materiais carbonosos. A evolução das razões I(D)/I(G), I(D′)/I(G) e I(D″)/I(G) possibilitou correlacionar o grau de desordem e a hibridização do carbono com a potência de escrita e a velocidade de deposição. Em potências mais elevadas, observou-se predominância da banda G, indicando maior organização e presença de domínios sp², compatível com a formação de óxido de grafeno parcialmente reduzido (rGO), conforme descrito por López-Díaz et al 1. Em potências intermediárias, a intensificação da banda D e o desaparecimento parcial da 2D indicaram aumento da desordem e da oxigenação, resultando em estruturas do tipo GO, de acordo com Sadezky et al 2 e Wu et al 3. Já em potências mais baixas, o reaparecimento discreto da banda 2D e a redução de I(D)/I(G) sugeriram a reorganização de regiões sp², indicando o início de processos de reestruturação e redução parcial. A escrita com o laser de 532 nm favoreceu a reorganização das redes de carbono e a diminuição dos grupos oxigenados, formando regiões grafíticas mais ordenadas. As amostras irradiadas com esse comprimento de onda apresentaram menores valores de I(D″)/I(G) e I(D*)/I(G), além de bandas G mais estreitas, evidenciando maior proporção de carbono sp² e caráter de rGO. Por outro lado, o laser de 405 nm produziu efeitos mais oxidantes e desordenados, resultando em maiores razões I(D)/I(G) e presença significativa das bandas D″ e D*, associadas a grupos C–O, C=O e C–OH, o que indica formação de GO funcionalizado com alta densidade de defeitos. Essa diferença de comportamento foi atribuída à maior energia dos fótons de 405 nm, capazes de romper ligações C–C e C–O e promover reações de oxidação local. As análises de fotoluminescência complementaram os resultados Raman, evidenciando emissões intensas no intervalo de 420–600 nm, relacionadas à recombinação radiativa em centros de emissão de natureza carbonílica e em nanodomínios semelhantes a pontos quânticos de carbono (CQDs). Os filmes tratados em torno de 240°C e escritos com potências intermediárias exibiram emissão branca sob excitação UV-vis, resultado da superposição de múltiplos centros emissivos e da combinação balanceada entre regiões sp² emissoras e grupos oxigenados. Esse comportamento demonstra o papel crucial da energia de escrita na modulação dos estados eletrônicos e na engenharia de emissões contínuas no espectro visível. A variação da velocidade de deposição também mostrou impacto significativo: filmes obtidos a 1,02 cm/min apresentaram maior uniformidade e resposta espectral mais intensa, enquanto velocidades mais altas (15,88 cm/min e 31,75 cm/min) resultaram em filmes com heterogeneidade estrutural mais acentuada, refletindo em maior dispersão dos valores de I(D)/I(G) e menor intensidade de emissão. Em conjunto, os resultados confirmam que a combinação entre o tratamento térmico e a escrita a laser constitui uma rota eficaz e controlável para ajustar o grau de oxidação, o ordenamento estrutural e as propriedades ópticas dos filmes à base de carbono. O entendimento detalhado dos processos de redução, oxidação e reorganização induzidos pelo laser permite direcionar a síntese de materiais luminescentes com características ajustáveis, explorando diferentes regimes de energia e morfologia. Os filmes obtidos apresentam potencial para aplicações em dispositivos optoeletrônicos e fotônicos, como LEDs brancos, sensores e revestimentos emissores sustentáveis, destacando-se pelo baixo custo e caráter ambientalmente amigável do método.
Polymeric films of acid and ethylene glycol: synthesis and structural and optical characterization
Keywords: Filmes luminescentes; Óxido de grafeno; Escrita a laser; Luminescent films; Graphene oxide; Laser writing